2022
DOI: 10.3389/fvets.2021.802479
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Serotonin Transporter in the Dog Intestine and Comparison to the Rat and Human Intestines

Abstract: Serotonin is crucial in gastrointestinal functions, including motility, sensitivity, secretion, and the inflammatory response. The serotonin transporter (SERT), responsible for serotonin reuptake and signaling termination, plays a prominent role in gastrointestinal physiology, representing a promising therapeutic target in digestive disorders. Serotonin transporter expression has been poorly investigated in veterinary medicine, under both healthy and pathological conditions, including canine chronic enteropath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
(112 reference statements)
2
2
0
Order By: Relevance
“…In agreement with Roberto Chiocchetti (2022), we hypothesize that the presence of serotonin in the cytoplasm of goblet cells may be due to specialized serotonin transporter (SERT) present in the goblet cells [53]. SERT is expressed by a variety of mucosal immune cells, including macrophages, mast cells, lymphocytes, dendritic cells [54], and intestinal epithelial cells, such as enterocytes [13,[55][56][57] and goblet cells [53]. Serotonin transporter phosphorylated is internalized and its expression can be altered in inflammatory bowel disease (IBD) [13,[57][58][59][60].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with Roberto Chiocchetti (2022), we hypothesize that the presence of serotonin in the cytoplasm of goblet cells may be due to specialized serotonin transporter (SERT) present in the goblet cells [53]. SERT is expressed by a variety of mucosal immune cells, including macrophages, mast cells, lymphocytes, dendritic cells [54], and intestinal epithelial cells, such as enterocytes [13,[55][56][57] and goblet cells [53]. Serotonin transporter phosphorylated is internalized and its expression can be altered in inflammatory bowel disease (IBD) [13,[57][58][59][60].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we demonstrated, for the first time, the presence of 5-HT in goblet cells cytoplasm of control samples, whereas the positivity to serotonin was few or absent in CD patients' epithelial goblet cells. In agreement with Roberto Chiocchetti (2022), we hypothesize that the presence of serotonin in the cytoplasm of goblet cells may be due to specialized serotonin transporter (SERT) present in the goblet cells [53]. SERT is expressed by a variety of mucosal immune cells, including macrophages, mast cells, lymphocytes, dendritic cells [54], and intestinal epithelial cells, such as enterocytes [13,[55][56][57] and goblet cells [53].…”
Section: Discussionsupporting
confidence: 85%
“…SERT expression is much higher in the small intestine than in the colon, In the intestinal epithelial cells, SERT is detected in the cytoplasm, being more concentrated in the upper portions of cells, but also was visible in the intracellular compartments, close to the basolateral membrane. Thus, SERT on the tips of the enterocytes makes luminal 5-HT uptake possible while its basolateral expression suggests 5-HT reuptake from the lamina propria [ 14 ]. Here, we have observed that TLR9 activation decreases SERT activity.…”
Section: Discussionmentioning
confidence: 99%
“…These mammals, just like all other animals, cannot form de novo the carbon skeletons of Cys, His, Ile, Leu, Lys, Met, Phe, Thr, Trp, Tyr, and Val, but can convert Phe into Tyr, Met into Cys, and Trp to serotonin (Wu 2022). Some metabolites of tyrosine (melanins) are crucial for the color of hair and skin health (Anderson et al 2002;Biourge and Sergheraert 2002;Yu et al 2001), whereas serotonin regulates animal behavior (Landsberg et al 2017) and intestinal function (Chiocchetti et al 2021). In addition, these two animal species, young or adult, are not capable of synthesizing sufficient arginine from glutamine/glutamate and proline (Burns et al 1981;Czarnecki and Baker 1984;Weber et al 1977;Yu et al 1996).…”
Section: Overview Of Protein and Aa Metabolismmentioning
confidence: 99%